EFFECT OF NANOSILVER PAINTING ON CONTROL OF HOSPITAL AIR-TRANSMITTED MICROORGANISMS - Naddafi, K; Jabbari, H; Chehrehei, M (Iranian journal of environmental health science & engineering, 2010)
Microorganisms, including bacteria and fungi, are among air-transmitted infectious agents at hospitals, which in addition to patients, can afflict hospital employees and visitors, and may result in economic burden and impact on human health. Although application of physical and chemical methods for control of microbial growth is not a new subject, but the use of nanotechnology and especially nanosilver painting is a new method applied in this area. This study was aimed to assess antibacterial and antifungal effects of nano-silver painting. Three rooms were selected in an infectious diseases unit of a university-based tertiary referral hospital affiliated to Tehran University of Medical Sciences. One of the rooms was painted with ordinary paint having no nano-particle (as control room) and the other two rooms were painted with two different 2% nanosilver paints ( one locally produced and other provided from abroad) provided from two different companies (as case rooms). Air sampling was carried out using a portable air pump (Quick Take 30 with constant rate between 10 and 30 L/min from 1 to 999 minutes) at pre-planned schedule. Each sampling was done in two minutes with the rate of 28.3 L/min. Samples were transferred on Blood agar (for total bacterial growth), EMB agar (for Gram negative bacterial growth) and Sabouraud>s Dextrose agar (for fungi detection) medias to study the culture results and Colony Forming Unit (CFU) count. Results, tested by ANOVAs and Kruskal-Wallis methods, indicated that there was no statistically significant reduction in the bacterial and fungal bio- burden between the control and case rooms and also between two types of paints by active sampling method. Moreover, there was no selective statistically significant change in bacterial and fungal species CFUs collected from the painted rooms by the above mentioned method. Study also revealed that there is no time trend change in bacterial bio- burden of the under study case and control rooms except for the first time zone (one month) of study duration. [PUBLICATION ABSTRACT]